Exploiting inter-organizational relationships in health care: A bibliometric analysis and literature review - Rocco Palumbo; Mohammad Fakhar Manesh; Massimiliano M. Pellegrini; Giulia Flamini (Administrative Sciences, 2020)
Inter-organizational relationships are high on the health policy agenda. Scholars and practitioners have provided heterogeneous views about the triggers of collaborative practices and the success factors that underpin the sustainability of inter-organizational relationships in the health care domain. The article proposes a literature review aimed at systematizing current scientific research that contextualizes inter-organizational relationships to health care. A mixed approach was undertaken, which consisted of a bibliometric analysis followed by a narrative literature review. A tailored search strategy on Elsevier's Scopus yielded 411 relevant records, which were carefully screened for inclusion in this study. After screening, 105 papers were found to be consistent with the study purposes and included in this literature review. The findings emphasize that the establishment and implementation of inter-organizational relationships in health care are affected by several ambiguities, which concern both the governance and the structuring of collaborative relationships. The viability and the success of inter-organizational relationships depend on the ability of both central and peripheral partners to acknowledge and address such ambiguities. Failure to do so involves an opportunistic participation to inter-organizational relationships. This endangers conflicting behaviors rather than collaboration among partners.
Keywords: 350; collaboration; cooperation; health care; inter-organizational relationship; network